2019
DOI: 10.1038/s41598-018-38281-0
|View full text |Cite
|
Sign up to set email alerts
|

MD001, a Novel Peroxisome Proliferator-activated Receptor α/γ Agonist, Improves Glucose and Lipid Metabolism

Abstract: Peroxisome proliferator-activated receptor (PPAR)-α/γ dual agonists have been developed to treat metabolic diseases; however, most of them exhibit side effects such as body weight gain and oedema. Therefore, we developed a novel PPARα/γ dual agonist that modulates glucose and lipid metabolism without adverse effects. We synthesised novel compounds composed of coumarine and chalcone, determined their crystal structures, and then examined their binding affinity toward PPARα/γ. We investigated the expression of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…Three different energy systems, including aerobic oxidative, anaerobic glycolytic, and phosphagen systems, are responsible for transforming chemical energy into physical force in skeletal muscle, thereby allowing humans to perform various physical activities (Frontera and Ochala, 2015;Wells et al, 2009). Secondly, along with other two organs, hepatic and adipose tissues, skeletal muscle is a representative organ to metabolize glucose, free fatty acid, and protein (Kim et al, 2019c). Therefore, skeletal muscle is a wellknown target organ not only for treating metabolic diseases and symptoms, such as obesity, type 2 diabetes, hyperglycemia, and hyperlipidemia but also for maintaining body temperature (Frontera and Ochala, 2015;Kim et al, 2019c).…”
Section: Introductionmentioning
confidence: 99%
“…Three different energy systems, including aerobic oxidative, anaerobic glycolytic, and phosphagen systems, are responsible for transforming chemical energy into physical force in skeletal muscle, thereby allowing humans to perform various physical activities (Frontera and Ochala, 2015;Wells et al, 2009). Secondly, along with other two organs, hepatic and adipose tissues, skeletal muscle is a representative organ to metabolize glucose, free fatty acid, and protein (Kim et al, 2019c). Therefore, skeletal muscle is a wellknown target organ not only for treating metabolic diseases and symptoms, such as obesity, type 2 diabetes, hyperglycemia, and hyperlipidemia but also for maintaining body temperature (Frontera and Ochala, 2015;Kim et al, 2019c).…”
Section: Introductionmentioning
confidence: 99%
“…PPARα agonists (e.g., fibrates) or PPARr agonists (e.g., thiazolidinedione) play important roles in the treatment of hyperlipidemia and type 2 diabetes in the clinic. PPARα/r dual agonists are also under development to treat more complex metabolic diseases, but some exhibit side effects and cause liver or cardiac dysfunction [64, 65]. In clinical trials, it has been demonstrated that supplementation with curcumin at a high dose is safe in humans [66, 67].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, primary human skeletal muscle cells were investigated together with the WRL68 cell line, representative of mature human hepatocytes, as well as differentiated 3T3L1 cells, representative of mature murine adipocytes. The combination of human hepatocyte cell lines and murine adipocyte cell lines has already been successfully used in previous studies [18,19].…”
Section: Discussionmentioning
confidence: 99%